Determinations Affecting The Quality Of Local Government Reports With Human Resources And Organizational Culture As Moderated Veriables - Anwar, Rapika; Ishak, Parmin (Gorontalo Accounting Journal, 2021)
Regional Government Financial Statement Quality Moderated with competence of human resource and organizational culture at regional work units (SKPD) of Gorontalo Province. This is a quanititative research by having regional work units of Gorontalo Province as the research object. Research samples are determinant by applying purposive sampling. Then, research data are collected through survey method by distributing questionnaire directly to employees of accounting division in 32 of Gorontalo Province and the results are processed using smart PLS.3.0. Research findings show that the implementation of accrual – based accounting, information technology has positive and significant influence on regional government financial statement quality and that is moderated with human resorce competence, and organizational culture.